An Ocean of Discovery: Biodiversity Beyond the Census of Marine Life - Snelgrove, Paul V. R. (Planta Medica, 2016)
The 70 % of Earthʼs surface covered by oceans supports significant biological diversity and immense untapped potential for marine bioproducts. The recently completed international Census of Marine Life (2000–2010) invested heavily in evaluating the diversity, abundance, and distribution of life in the ocean but concluded that at least 50 % and potentially > 90 % of marine species remain undescribed by science. Despite this potential, and numerous successes spanning pharmaceuticals, nutraceuticals, anti-foulants and adhesives, biofuels, biocatalysts (enzymes), and cosmetics, several impediments have slowed marine bioproduct development. First, the sheer size of the ocean constrains comprehensive exploration. Second, marine taxonomists and ecologists generally do not focus on the most promising groups for bioproduct development. Third, the geographic mismatch between (often remote) biodiversity hotspots and science capacity limit discovery. Despite these challenges, new ocean sampling tools (digital imaging, remote vehicles, genetic approaches, in situ samplers), many developed or improved during the Census of Marine Life, should enhance future marine biodiversity and thus marine bioproduct discovery.
Keywords: biodiversity; taxonomy; invertebrates; Census of Marine Life; marine bioprospecting; biogeography